Answer:
Step-by-step explanation:
To simplify this expression, first use the distributive property to distribute .
Simplify.
Combine like terms, and .
The simplification of is .
I hope this helps ^^
Good luck
-1(5x+1)
-5x-1
the (-) in front is just a short way to put (-1)
Step-by-step explanation:
Equating,
Placing it,
The top-left graph goes with the bottom-right equation, y=90(1/4)^x
The bottom-left graph goes with the top-right equation, y = 120(3/4)^x
The top-right graph goes with the bottom-left equation, y = 120(1/4)^x
The bottom-right graph goes with the top-left equation, y = 90(3/4)^x
y=90(1/4)^x has a larger percent decrease than y = 90(3/4)^x
cause if you multiply a number by 1/4, that's smaller than multiplying number by 3/4. so y=90(1/4)^x decreases really fast
same with the y = 120(3/4)^x ones
Yes Karis is correct I hope this helps and if its wrong let me know but I'm sure I'm correct